INFECTION ABILITY OF THE ENTOMOPATHOGENIC FUNGUS CORDYCEPS MILITARIS ON LARVAE AND PUPAE OF NETTLE CATERPILLAR Setothosea asigna (Lepidoptera: Limacodidae) - Sat Rahayuwati; Heri Azwar Fadilah Sarumpaet; Gerson Halawa; Bayu Pratomo (Prodi Agroteknologi Fakultas Agro Teknologi Universitas Prima Indonesia, 2026)
Combination between organochlorine and clean weeding is suggested for nettle caterpillar outbreak in oil palm plantation. Insecticides lead to natural enemies died, clean weeding caused food shortages and lack of refuge areas for its natural enemies. Cordyceps militaris is one of fungus biological controls to Setothosea asigna. This fungus is possible to produce in large quantities on maize. C. militaris is typically sprinkled or sprayed onto palm circle as pupae targeted. Several studies have shown that C. militaris can also infect larval stages of S. asigna in the laboratory. This study aim is to confirm that C. militaris in maize media, at optimal dose 15 g/100 ml (based on previous study) could induce infection on both S. asigna larval and pupal stages. Four days after application (‘daa’), 100% mortality was observed in S. asigna larvae. Dead larvae were characterized by brown coloration, larval excretion, intact but fragile larvae, and mycelial growth. Infected pupae are not visible externally because they are protected by cocoons. After 16 ‘daa’ there were difference between infected and control pupae. Infected pupae were still in the final larval stage, covered in mycelium, and died. Control pupae had developed into adults with wings, head, and body. C. militaris on maize and PDA medium was white or lacked pigment. C. militaris derived from infected larvae and pupae were able to grow and produce greenish conidia on PDA. C. militaris conidia from larvae had already formed in large quantity after 6 days on PDA, while the pupae were only in the early stages of conidia formation. C. militaris derived from maize formed only mycelium without conidia. This study concluded that C. militaris could infect both larval and pupal stages of S. asigna.